A is for Arak - Weinfeld, Oliver; Acetate (Firm); FeelSales (Firm) ([United Kingdom] : [Acetate], 2019)
A short yet sweet film about booze in Lebanon. From Beirut to the Bekaa Valley, exploring the history, distillation and appeal of the grandfather of all spirits - Arak. --
Originally released as a motion picture in 2019.
Faouzi Issa, Michael Karam, Andrea Gearra, Boutros Gearra, Avedis Khederlarian.
Cinematographer, Giacomo La Monca ; editor, Oliver Weinfeld ; music, Paul Tyan.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 26, 2021)
Keywords: Arak; Short films; Documentary films; Nonfiction films; Internet videos; Streaming video